Tribological performance of CrAlYN-based nanocomposite coatings - Ong, Winston Bao De (2017)
The incorporation of Y has been known to improve the oxidation resistance and thermal stability of Cr-based nitride hard coatings. This is especially important in high temperature engineering applications (e.g. > 1000°C). In particular, the tribological properties of Y-doped coatings are of significant interest. Hence, this project aims to study the tribological performance of CrAlYN hard coatings with varying Y-doped content.